Effective CAL: theory and practice - Hassan Khan (Association for Learning Technology, 1995)
Modern-day authoring systems have made the production of CAL applications so easy that people with little computer literacy are able quite quickly to create elaborate multimedia applications. The point, however, is that while so many of us have become authors in the past few years, the objective of our creations has been somewhat missed. It is all to easy to see visually impressive multimedia CAL, and to convince ourselves that they represent good CAL material. An application may be quickly sanctioned, produced and implemented at universities, then attention is focused on to the next project. While evaluation is normally costed into a project, various constraints, such as shifting personnel or additional demands on funds, limit the evaluation of the application to ascertain whether the investment of producing it was worthwhile. The Hypertext Support Unit (HSU) at the University of Kent was set up in 1992 to promote the pervasive use of hypertext across the campus. In its role as a support unit, it facilitates the development of CAL material in all disciplines in close collaboration with the content specialists, i.e. the lecturers. The HSU, along with many other units or departments, produce many CAL application paying attention to the aesthetics of interface design, but largely glossing over the learning instructions so vital to good CAL applications in harnessing the potential of multimedia in an educational environment. Too many people put a linear book on-line, give it some bookmarks, and call it hypertext; worse yet, they add a few scanned-in photographs and a soundtrack and call it multimedia (Fisher, 1994).